Polyethylene versus cotton cap as an adjunct to body wrap in preterm infants. Issue 7 (20th June 2017) - Shafie, Hashim; Syed Zakaria, Syed Zulkifli; Adli, Ali; Shareena, Ishak; Rohana, Jaafar
Abstract: Background: Occlusive body wrap using polyethylene plastic applied immediately after birth had been shown to reduce hypothermia among preterm infants. Various adjunct methods have been studied in an attempt to further reduce the incidence of hypothermia. This study was conducted to determine whether polyethylene cap is more effective than cotton cap as an adjunct to polyethylene occlusive body wrap in reducing hypothermia in preterm infants. Methods: The subjects consisted of preterm infants 24–34 weeks' gestation born at Universiti Kebangsaan Malaysia Medical Centre. Infants were randomly assigned to NeoCap or control groups. Infants in both groups were wrapped in polyethylene sheets from the neck downwards immediately after birth without prior drying. Infants in the control group had their heads dried and subsequently covered with cotton caps while infants in the NeoCap group had polyethylene caps put on without drying. Axillary temperature was measured on admission to the neonatal intensive care unit (NICU), and after having been stabilized in the incubator. Results: Among the 80 infants recruited, admission hypothermia (axillary temperature <36.5°C) was present in 37 (92.5%) and in 40 (100%) in the NeoCap and control groups, respectively. There was no significant difference in mean temperature on NICU admission between the two groups (35.3 vs 35.1°C, P = 0.36). Mean post‐stabilization temperature, however, was significantly higher in the NeoCap group (36.0 vs 35.5°C, P = 0.01). Conclusion: Combined use of polyethylene body wrap and polyethylene cap was associated with a significantly higher mean post‐stabilization temperature compared with polyethylene body wrap and cotton cap.